HD 121135: FEATURES OF ITS CHEMICAL COMPOSITION - Mishenina, T.; Usenko, I.; Kniazev, A.; Kovtyukh, V. (Одеські астрономічні публікації, 2020)
Low metallicity star HD121135 ([Fe/H] = -1.5) have been investigated spectroscopically. Its atmos- pheric parameters and elemental abundances have been determined, including elements of neutron (n-) capture processes, which are the keys in the study of early Galaxy enrichment. Na, Mg, Ni, Co, Sr, Y, Zr, Mo, Ba, La, Ce, Pr, Sm, Eu, Gd, Dy, Ho, Os, Th abundances were calculated using the synthetic spectrum method, factoring in the hy- perfine structure (HFS) for the Eu II lines. Si, Ca, Sc abun- dances were determined using the equivalent widths of their lines. The carbon content was computed by the molec- ular synthesis fitting for the region of CH (4300-4330 ÅÅ). For the abundances determinations of C, Na, Mg, Ba, and Th the NLTE corrections have been applied. We have determined for the first time the abundances of several n-capture elements and found that the behaviors of these elements do not show a significant trend with increasing atomic number. The elements ratios of [Eu/Fe] = 0.06, [Ba/Eu] = 0.13, [Sr/Ba] = - 0.05 do not support the HD121135 status as a r-process enrichment star. We have obtained the thorium abundance [Th/Fe] = 0.26. The car- bon content confirms the effect of canonical additional mixing in this star.